FOSTERING INTRINSIC MOTIVATION IN EFL LEARNERS THROUGH DUOLINGO’S GAMIFICATION: A QUALITATIVE STUDY - Amalia, Lena; Seinsiani, Izzati Gemi (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
Motivation plays a crucial role in English as a Foreign Language (EFL) learning, particularly in contexts with limited exposure to English outside the classroom. Although gamified language learning applications such as Duolingo are widely used, previous studies have largely emphasized extrinsic motivation and quantitative approaches. This study aimed to explore how Duolingo’s gamification fosters intrinsic motivation in EFL learners through the lens of Self-Determination Theory, focusing on autonomy, competence, and relatedness. A descriptive qualitative design was employed involving ten seventh-semester EFL university students from Universitas Negeri Semarang who were active Duolingo users. Data were collected through semi-structured interviews and an SDT-based questionnaire and analyzed using thematic analysis. The findings indicate that Duolingo’s gamification supports intrinsic motivation by creating an enjoyable, flexible, and engaging learning environment. Most participants reported using Duolingo primarily for personal enjoyment rather than external rewards, suggesting a shift toward intrinsic motivation. Autonomy and competence emerged as the most influential factors, while relatedness showed varied effects among learners. Overall, this study provides qualitative evidence that supporting learners’ psychological needs through gamification can enhance intrinsic motivation in EFL learning contexts.Keyword: Duolingo; EFL learners; intrinsic motivation; Self-Determination Theory